The Privacy Paradox: Exploring the role of privacy concerns and perceived benefits in mobile app usage - Keskimäki, Anniina (2025)
Nowadays consumers are using mobile phones and apps daily, leaving tracks of data be-hind with every click. Marketers utilize this data with advanced technology, enabling marketers to conduct personalized marketing, which is nowadays crucial for successful marketing. Mobile apps offer a unique platform, where consumers are accessible continuous-ly, and ads in apps are crucial for free apps to run. However, data collection raises privacy concerns, which affect consumers’ information disclosure, and furthermore, their mobile app usage. Since marketers rely on consumer data and users, this is a problem to be stud-ied. Consumers’ decisions are not always rational. Despite expressing privacy concerns, they disclose personal information, especially in the presence of incentives. This phenom-enon is referred to as the privacy paradox. This study examines consumers’ debate between their privacy concerns and per-ceived benefits when they encounter in-app mobile marketing, and how these factors af-fect their mobile app usage. Also, this study seeks understanding of the factors affecting privacy concerns and perceived benefits, as well as examining whether consumers use mobile apps despite reporting privacy concerns. Quantitative research method was cho-sen for this study, and 105 responses were gathered using Webropol questionary. The re-sponses were analyzed using IBM SPSS and IBM SPSS Amos 26 software. The results of this study increase the understanding of privacy paradox phenome-non and factors affecting mobile app usage. The study highlights that while consumers experience privacy concerns and these concerns negatively impact their mobile app usage, they use apps. Interestingly, despite literature proposing control and fairness decreasing these concerns, this study did not support previous findings. Instead, trust appears as a factor reducing privacy concerns. Although perceived benefits are often anticipated to in-crease mobile app adoption and usage, these findings indicate that they do not necessarily lead to increased mobile app usage. Finally, privacy concerns are not equivalent among all users, but vary in different age groups, suggesting that demographic factors have an im-pact on how privacy is perceived.